Viewing the Ediacaran biota as a failed experiment is unhelpful - Dunn, F; Liu, A (Springer Nature, 2019)
Macroscopic organisms from the late Ediacaran period have often been described as failed experiments in the history of life. We argue that the field of Ediacaran palaeobiology should dispense with unhelpful historical classification schemes and embrace phylogenetic systematics if we are to establish the evolutionary relevance of these fossils.